Comparison of Renal Complications between Endografts with Suprarenal and Infrarenal Fixation. (July 2017) - Zettervall, S.L.; Soden, P.A.; Deery, S.E.; Ultee, K.; Shean, K.E.; Shuja, F.; Amdur, R.L.; Schermerhorn, M.L.
Abstract : Objectives: Surgeons have multiple grafts options available for the endovascular treatment of abdominal aortic aneurysm (EVAR), and some hypothesize that suprarenal fixation endografts may result in higher rates of renal complications than infrarenal endografts. This study aimed to compare the outcomes of contemporary suprarenal and infrarenal endografts. Methods: The Targeted Vascular Module of the National Surgical Quality Improvement Project was utilised to identify patients undergoing EVAR for infrarenal aneurysm from 2011 to 2013. Pre-operative and operative variables and 30 day outcomes were compared among suprarenal (Zenith and Endurant) and infrarenal fixation devices (Excluder). Renal complications included creatinine increase > 2 mg/dL or new dialysis, as defined by NSQIP. Multivariate regression was completed to account for patient demographics, comorbidities, and operative characteristics. Results: A total of 3587 patients were evaluated including 2273 (63%) with suprarenal grafts and 1314 (37%) with infrarenal grafts. Patients with suprarenal grafts were less commonly white (84% vs. 88%, p  < .01) and more commonly male (83% vs. 80%, p  = .03). There were no differences in age or comorbidities. Renal complications (1.1% vs. 0.1%, p  < .01) and length of stay more than 2 days (34% vs. 25%, p  < .01) occurred more commonly after suprarenal fixation. After adjustment, suprarenal grafts had significantly higher rates of renal complications (OR, 12.0; 95% CI, 1.6–91) and length of stay more than 2 days (OR, 1.4; 95% CI, 1.2–1.7). Conclusion: Overall rates of renal complications following EVAR are low. Patients selected for suprarenal stent grafts are at increased risk of renal complications and prolonged length of stay, which may be due to selection bias, deployment techniques, or the presence of a bare stent overlying the renal arteries. Further studies are necessary to evaluate the mechanism and duration of renal dysfunction and important long-term outcomes of interest.